2018
DOI: 10.1002/cbic.201700323
|View full text |Cite
|
Sign up to set email alerts
|

A Thiolactone Strategy for Straightforward Synthesis of Disulfide‐Linked Side‐Chain‐to‐Tail Cyclic Peptides Featuring an N‐Terminal Modification Handle

Abstract: The development of straightforward and versatile peptide cyclisation methods is highly desired to meet the demand for more stable peptide-based drugs. Herein, a new method for the synthesis of side-chain-to-tail cyclic peptides with the simultaneous introduction of an N-terminal handle, based on the introduction of an N-terminal thiolactone building block, is described. A primary amine liberates a homocysteine analogue from the thiolactone building block, which further enables cyclisation of the peptide throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…As it was already demonstrated previously by our group that a large variety of side chains can be introduced to the oligomeric backbone by varying the aldehyde component in the P-3CR, this study was limited to three different aldehydes to generate " [ABC] x "-sequences. 29,30,34,35 Using L1 and L2, a two-step, iterative cycle was developed, consisting of a TAD-based Diels-Alder reaction, followed by the P-3CR (Scheme 1). Both reactions reached quantitative conversions and yields and were carried out both on the solid phase and in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was already demonstrated previously by our group that a large variety of side chains can be introduced to the oligomeric backbone by varying the aldehyde component in the P-3CR, this study was limited to three different aldehydes to generate " [ABC] x "-sequences. 29,30,34,35 Using L1 and L2, a two-step, iterative cycle was developed, consisting of a TAD-based Diels-Alder reaction, followed by the P-3CR (Scheme 1). Both reactions reached quantitative conversions and yields and were carried out both on the solid phase and in solution.…”
Section: Resultsmentioning
confidence: 99%
“…6,24 A common route towards sequence-defined oligomers, offering full control over each monomer unit, is the iterative synthesis approach. 7,[25][26][27][28][29][30][31][32] This step-by-step growth of the macromolecule is necessary to ensure a perfectly defined sequence as well as monodispersity. Whilst many different approaches exist, the use of multi-component reactions seems to be a logical choice within this area and such reactions have indeed been shown to be highly effective tools for the synthesis of sequence-defined macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclization is a type of peptide modification that involves forming a covalent bond between the N‐ and C‐termini of a peptide, resulting in a cyclic structure. Cyclic peptides have gained significant attention in biomedicine due to their unique properties and diverse applications (Van Lysebetten et al., 2018). One key advantage of cyclic peptides is their enhanced stability compared to linear peptides (Wang & Craik, 2018).…”
Section: Peptide Modificationsmentioning
confidence: 99%
“…With SPPS and further chemical modifications, various side-chain-involved cyclization tactics through lactam bridges (Taylor, 2002), disulfide bonds (Postma and Albericio, 2014), and thiolactone linkage (Van Lysebetten et al, 2018) have been reported in the past two decades. In contrast, SPPS of amide bond-joined backbone macrocyclic peptides proved to be difficult due to the limitation of acyl-derivatives that can react with the solid phase and C-terminal residue.…”
Section: Solid-phase Synthesis Of Backbone Macrocyclic Peptidesmentioning
confidence: 99%